Unfavourable plasma and erythrocyte phospholipid fatty acid profile in elite amateur boxers - Tepsic, J.; Vucic, V.; Arsic, A.; Mazic, S.; Djelic, M.; Glibetic, M. (European Journal of Sport Science, 2013)
Research on possible physiological changes as a consequence of a specific lifestyle and long-term strenuous exercise in boxing has been sparse. We determined plasma and erythrocyte phospholipid (PL) fatty acids (FA) profile of 16 elite amateur male boxers (22.4±3.3 years of age), and compared them with a control group composed of 19 sedentary (24.4±3.4) year-old men. The percentages of total saturated fatty acids (SFA) and monosaturated FA in plasma phospholipids were significantly higher (P <0.001) in boxers compared to the control group. On the other hand, all studied polyunsaturated fatty acids (PUFA) in plasma PL with the exception of eicosapentaenoic acid (EPA, 20:5, n-3) and docosatetraenoic acid (DTA, 22:4, n-6) were significantly lower in boxers than in sedentary men. Total PUFA, n-6 PUFA and n-3 PUFA were also significantly lower in boxers (P <0.001), whereas the n-6/n-3 ratio was higher in boxers than in control group (P <0.01). Boxers had significantly higher proportion of all SFA in erythrocyte PL compared to the control group (P <0.05). In addition, the percentage of linoleic acid was lower in boxers' erythrocyte PL than in the control group (P <0.05). The results show two potentially unfavourable main features of the FA profile of boxers, that is, a higher n-6/n-3 ratio in plasma PL and a higher percentage of SFA in both plasma and erythrocyte phospholipids compared to controls. As SFA correlates directly with the incidence of cardiovascular disease and high n-6/n-3 ratio has been shown to stimulate carcinogenesis and modulate inflammation and autoimmunity, this profile could be detrimental to the health of boxers. The mechanism underlying these differences requires further investigation; however the results suggest benefits of nutritional intervention.